Heliopsis suffruticosa (Compositae, Heliantheae), una nueva especie del occidente de Zacatecas - Ramírez-Noya, David; González-Elizondo, M. Socorro; Molina-Torres, Jorge (Instituto de Ecología, A.C., 2011)
Heliopsis suffruticosa is described from the Sierra de Sombrerete, in western Zacatecas, Mexico, growing in pinyon woodland on limestone. It differs from other species in the genus in having suffruticose habit, narrowly lanceolate to linear leaves with entire to sparsely serrulated margin, and peduncles gradually enlarged towards the apex, a combination of characters shared with some species of Zinnia. A key to distinguish among the Mexican species of perennial Heliopsis is presented. As other Heliopsis species, H. suffruticosa roots contain alkamides, in this case five diacetylenic conjugated next to a group methyl in the omega position, isobutyl alkamides.